Pengaruh Digital Marketing Terhadap Kinerja Perusahaan : Review Literatur Sistematik - Syamsul Hidayat, Mohamad; Eny Setyariningsih; Budi Utami (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) - Institut Teknologi dan Bisnis Semarang, 2024)
In modern marketing in the digital era, companies must adapt to rapidly developing technological changes. Consumers can get information more quickly via the internet. Companies that are able to provide information more quickly via digital have an easier time winning the competition. Digital marketing has recently been able to influence consumer behavior and company performance. There are several different studies and discussions about the influence of digital marketing. with companies. Therefore, the aim of this article is to provide a more concrete picture of the influence of digital marketing on company performance through a systematic literature review of 1200 articles. Consisting of 200 Scopus indexed publication articles and 1000 articles via Google Scholar. Of these 1200 articles We selected those that had the same topic regarding digital marketing. Then we selected again at least 20 quotes. Then we selected again the 20 most relevant published articles from 2012 to 2023. The findings show that in general digital marketing has an impact on company performance.